Pseudomonas aeruginosa ExoT induces G1 cell cycle arrest in melanoma cells. (14th April 2021) - Mohamed, Mohamed F.; Wood, Stephen J.; Roy, Ruchi; Reiser, Jochen; Kuzel, Timothy M.; Shafikhani, Sasha H.
Abstract: Recently, we demonstrated that Pseudomonas aeruginosa Exotoxin T (ExoT) employs two distinct mechanisms to induce potent apoptotic cytotoxicity in a variety of cancer cell lines. We further demonstrated that it can significantly reduce tumour growth in an animal model for melanoma. During these studies, we observed that melanoma cells that were transfected with ExoT failed to undergo mitosis, regardless of whether they eventually succumbed to ExoT‐induced apoptosis or survived in ExoT's presence. In this report, we sought to investigate ExoT's antiproliferative activity in melanoma. We delivered ExoT into B16 melanoma cells by bacteria (to show necessity) and by transfection (to show sufficiency). Our data indicate that ExoT exerts a potent antiproliferative function in melanoma cells. We show that ExoT causes cell cycle arrest in G1 interphase in melanoma cells by dampening the G1/S checkpoint proteins. Our data demonstrate that both domains of ExoT; (the ADP‐ribosyltransferase (ADPRT) domain and the GTPase activating protein (GAP) domain); contribute to ExoT‐induced G1 cell cycle arrest in melanoma. Finally, we show that the ADPRT‐induced G1 cell cycle arrest in melanoma cells likely involves the Crk adaptor protein. Our data reveal a novel virulence function for ExoT and further highlight the therapeutic potential of ExoT against cancer.